JSW Steel's Ispat acquisition (C) : the turnaround strategy - Sharma, Sunil, (SAGE Knowledge. Cases., 2016)
JSW Steel has made the decision to retain Ispat, and attempt to resolve its many problems. JSW develops a comprehensive strategy to develop Ispat into a profitable subsidiary. To do this, many economic, management, and process changes had to be put into place, and JSW had to gain the confidence and support of its shareholders.